2017
DOI: 10.4049/jimmunol.1601503
|View full text |Cite
|
Sign up to set email alerts
|

AKT2 Regulates Pulmonary Inflammation and Fibrosis via Modulating Macrophage Activation

Abstract: Idiopathic pulmonary fibrosis (IPF) is a highly lethal pathological process that is characterized by inflammation, fibroblast accumulation, and excessive collagen deposition. Although AKT2-mediated signaling pathways modulate inflammatory responses, their role in IPF has not been defined. We report that AKT2 deficiency () protected against bleomycin-induced pulmonary fibrosis and inflammation. Adoptive transfer of wild-type macrophages or administration of IL-13 to mice could restore pulmonary fibrosis. In res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 55 publications
2
60
0
Order By: Relevance
“…BLM causes damage to the alveolar epithelial cells, leading to an interstitial inflammatory response within the first week after its administration. 19,30 However, we found there were few significant and pathological conditions. 32,33 One important downstream target protein is FoxO1, which can be deactivated through phosphorylation at its three putative phosphorylation sites for Akt.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…BLM causes damage to the alveolar epithelial cells, leading to an interstitial inflammatory response within the first week after its administration. 19,30 However, we found there were few significant and pathological conditions. 32,33 One important downstream target protein is FoxO1, which can be deactivated through phosphorylation at its three putative phosphorylation sites for Akt.…”
Section: Discussionmentioning
confidence: 70%
“…Inflammatory responses are a critical mechanism for PF progression. BLM causes damage to the alveolar epithelial cells, leading to an interstitial inflammatory response within the first week after its administration . However, we found there were few significant changes in BLM‐induced inflammation after lanatoside C administration (Figure A‐D) and that the effect of lanatoside C in regulating the development of BLM‐induced PF is not through suppressing the inflammatory response.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…17 Nie et al have demonstrated that FOXO3a represses interleukin-13 transcription in macrophages to protect against bleomycin-induced pulmonary inflammation and fibrosis. 18 In addition, it has been shown that FOXO3a is capable of inhibiting the NLRP3 inflammasome by potentiating the transcription of Bim in liver macrophages (Kupffer cells). 19 Recently, genome-wide meta-analysis indicates that interplay between FOXO3a and certain MHC II molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%